Positioning Of Legal Philosophy To Maintain The Dignity Of Law Enforcement - Boy Nurdin; Juristo Juristo; Wahyu Widodo; Apriaji Setyawan; Ubaidilah Ishaq; Satria Dwi Rahardja; Anwar Sunarjo (PT Publikasiku Academic Solution, 2024)
The enforcement of law is an integral aspect of the legal system's functioning, and it is often criticized with phrases like